Tanggapan Mahasiswa dalam Menanggapi Stabilitas Kesehatan Mental Remaja di Masa Pandemi - Zahra Salsabilla, Anggina; Moestafidz, Chalieq; Alifa Kamal, Nazla (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2025)
Across the world, including in Indonesia, the COVID-19 pandemic has had a major impact on adolescent mental health. The focus of this study is how online learning impacts adolescents' mental health during the pandemic. Students of Public Health Science Study Program were surveyed using a qualitative approach through literature review and structured interviews. The results show that some of the main factors affecting mental health are social isolation, academic pressure, and lack of access to technology. Adolescents may experience stress, anxiety, depression and learning fatigue. In addition, when they serve as a source of support or as a trigger for adverse social comparisons, social media has controversial effects. Online learning has become more difficult due to issues such as poor signal, expensive internet quotas, and limited learning facilities. However, the pandemic also gives us an opportunity to be more aware of the importance of mental health. Some teenagers have started to cope with stress by exercising, pursuing hobbies, and getting closer to their families. According to research, governments and educational institutions should provide counseling services, reduce academic load, and improve teacher training. So while the pandemic has caused a lot of problems, taking the right actions can help mitigate its effects and promote greater awareness about the importance of maintaining teenagers' mental health.